2021
DOI: 10.18415/ijmmu.v8i5.2670
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Utilitarian Value and Hedonic Value on Customer Loyalty with Customer Satisfaction As an Intervening Variable: Empirical Evidence from Indonesia

Abstract: The purpose of this study was to build an understanding of the influence of utilitarian values and hedonic values on customer satisfaction and customer loyalty at hypermarket in Pamekasan Regency, Jawatimur Province, Indonesia. Type of research is Explanatory Research. Data collection using a questionnaire. The sampling technique used purposive sampling. The number of samples was 250 consumers and data analysis used the Structural Equation Model (SEM) with AMOS software. The results of this study indicate util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The analysis shows that customer satisfaction significantly and positively affects client loyalty. These findings are consistent with those of Ulfa & Mayliza, (2019) and Zainurrafiqi et al (2021), who found that customer satisfaction has a significant impact on customer loyalty.…”
Section: Customer Satisfaction On Customer Loyaltysupporting
confidence: 93%
“…The analysis shows that customer satisfaction significantly and positively affects client loyalty. These findings are consistent with those of Ulfa & Mayliza, (2019) and Zainurrafiqi et al (2021), who found that customer satisfaction has a significant impact on customer loyalty.…”
Section: Customer Satisfaction On Customer Loyaltysupporting
confidence: 93%
“…Initiatives like TikTok Shop reflect efforts to create a more dynamic digital commerce ecosystem. (Zainurrafiqi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Utilitarian value is a value that shows consumer interest in using a product based on the usefulness, nature, and practical function of the product because there is a need that must be met. Utilitarian value can be defined as the monetary benefits and convenience received by consumers when making transactions for a product or service (Rintamäki et al, 2006;Zainurrafiqi et al, 2021). From the monetary side, consumers tend to want to pay a low price to get the maximum benefit from the product or service.…”
Section: Introductionmentioning
confidence: 99%
“…Exploration and freedom will make them feel fulfilled (To et al, 2007). Therefore, delivering the hedonic aspect to consumers will provide a good experience when shopping as well as have a positive impact on customer satisfaction (Rintamäki et al, 2006;Ryu et al, 2010;Turley & Milliman, 2000;Zainurrafiqi et al, 2021;).…”
Section: Introductionmentioning
confidence: 99%